2018
DOI: 10.5897/err2018.3494
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to learn Turkish in foreign students with different thinking styles in terms of functional and formal aspects

Abstract: The aim of this study was to determine the level of motivation to learn Turkish among foreign students with different thinking styles in terms of the functional and formal aspects of these thinking styles. The survey model was used in the study. The participants in the study were 51 foreign students (33 female, 18 male) who were studying at the TÖMER (Türkçe Öğretim Merkezi [Center of Turkish Language Teaching]) at Gaziantep University in the 2016-2017 academic year and who were selected by the convenience sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Although the level of the effect of the detected differences is low, this difference is in favor of female students. Some studies conducted in Turkey (Ertan, 2008;Pulat, 2010) and other countries (Chang, 2005;Demir, 2022;Mori & Gobel, 2006;Nikitina & Furuoka, 2005;Peacock, 1997;Varisoglu, 2018) have found that female students are more motivated in comparison to male students.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Although the level of the effect of the detected differences is low, this difference is in favor of female students. Some studies conducted in Turkey (Ertan, 2008;Pulat, 2010) and other countries (Chang, 2005;Demir, 2022;Mori & Gobel, 2006;Nikitina & Furuoka, 2005;Peacock, 1997;Varisoglu, 2018) have found that female students are more motivated in comparison to male students.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%